2017
DOI: 10.1111/1911-3846.12327
|View full text |Cite
|
Sign up to set email alerts
|

Auditors’ Joint Engagements and Audit Quality: Evidence from Italian Private Companies

Abstract: This study examines the effect of auditors’ collaboration in joint audit engagements on knowledge transfer, auditor expertise, and audit outcomes. I employ a unique sample of Italian private companies whose financial statements are jointly audited by three individual auditors and use measures from the network literature to capture the intensity of interactions between these auditors. I find a positive association between several audit quality proxies and auditors’ collaboration in multiple joint engagements. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 104 publications
(231 reference statements)
1
30
1
Order By: Relevance
“…Furthermore, while extant studies have investigated the influence of auditing characteristics in terms of audit approach (Alfraih, 2016;Bianchi, 2018;Habib et al, 2019) as well as audit quality (Afify, 2009;Ashton et al, 1989;Bamber et al, 1993;Dao and Pham, 2014;Taktak and Mbarki, 2014), they have not considered auditing characteristics as mediating variables. Studies on audit approach vary, with some using joint audit and others using change of auditors (see Habib et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, while extant studies have investigated the influence of auditing characteristics in terms of audit approach (Alfraih, 2016;Bianchi, 2018;Habib et al, 2019) as well as audit quality (Afify, 2009;Ashton et al, 1989;Bamber et al, 1993;Dao and Pham, 2014;Taktak and Mbarki, 2014), they have not considered auditing characteristics as mediating variables. Studies on audit approach vary, with some using joint audit and others using change of auditors (see Habib et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that increased auditor concentration in local audit markets improve audit quality (Choi et al 2017). Other factors improving audit quality examined were identified as: enterprise system implementation (Pincus et al 2017); average education level (Beck et al 2018); joint engagements, facilitating knowledge transfer and auditor expertise (Chi et al 2017;Bianchi, 2018); city-industry specialists (Chen et al 2018); expert advice of higher quality (Wright and Bhattacharjee, 2018); reinforcing the image of auditors as independent to the investor community for the annual general meeting (Johed and Catasus, 2018). Finally, the empirical study conducted by Chen et al (2017) found that investors reduce private information collection in response to higher audit quality.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study (Lobo et 2015;Bianchi, 2018) showed that the use of two auditors to conduct audit work was positively associated with higher profit quality as well as higher audit fees, lower financial statements, lower expenses, and timely recognition of economic losses.…”
Section: Optional Joint Review In Egyptmentioning
confidence: 99%